Hypoxia-Responsive Azobenzene-Linked Hyaluronate Dot Particles for Photodynamic Tumor Therapy - Sohyeon Lee; Yoonyoung Kim; Eun Seong Lee (MDPI AG, 2022)
In this study, we developed ultra-small hyaluronate dot particles that selectively release phototoxic drugs into a hypoxic tumor microenvironment. Here, the water-soluble hyaluronate dot (dHA) was covalently conjugated with 4,4'-azodianiline (Azo, as a hypoxia-sensitive linker) and Ce6 (as a photodynamic antitumor agent), producing dHA particles with cleavable Azo bond and Ce6 (dHA-Azo-Ce6). Importantly, the inactive Ce6 (self-quenched state) in the dHA-Azo-Ce6 particles was switched to the active Ce6 (dequenched state) via the Azo linker (-N=N-) cleavage in a hypoxic environment. In vitro studies using hypoxia-induced HeLa cells (treated with CoCl2) revealed that the dHA-Azo-Ce6 particle enhanced photodynamic antitumor inhibition, suggesting its potential as an antitumor drug candidate in response to tumor hypoxia.